A Systematic Literature Review of Effect Self-Compassion on Students with Learning Disabilities - Dian Atnantomi Wiliyanto; Gunarhadi Gunarhadi; Sunardi Sunardi; Munawir Yusuf (Ianna Journal of Interdisciplinary Studies)
Background: Self-compassion is crucial for the well-being of students with impairments. However, only some studies have systematically reviewed its effects on academic and social outcomes.